The social construction of sexuality - Seidman, Steven (W.W. Norton & Company, 2015)
In The Social Construction of Sexuality, Steven Seidman investigates the political and social consequences of privileging certain sexual practices and identities while stigmatizing others. Addressing a range of topics from gay and lesbian identities to sex work, Seidman delves into issues of social control that inform popular beliefs and moral standards. The new Third Edition features three new chapters that focus on the changing cultures of intimacy, the promise and perils of cyber intimacies, and youth struggles to negotiate independence and intimate solidarity.– Provided by Publisher.
Section: xv, 301 pages ; 21 cm
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; hétérosexisme; intimité; premier cycle; privilèges; sciences humaines; sexologie; sexualité; soc2014; systèmes d'oppressions; thématiques; travail; travail du sexe

Queer theory/sociology - Seidman, Steven (Blackwell, 1996)
Bringing together some of the classic sociological statements and the new sociology of homosexual desire, this book points to new synthetic approaches to queer studies. It aims to productively engage the pioneering work of queer theorists.
Section: xiii, 450 pages ; 24 cm.
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; approches et analyses; cours; discipline; premier cycle; périodes historiques; queer; sciences humaines; soc2014; sociologie; sofia; thématiques